Cultural Identity in Intercultural Communication: Analyzing the Impact of Linguistic Choices in Multilingual Interactions - Shaikh, Hasan (LET: Linguistics, Literature and English Teaching Journal, 2024)
In an era characterized by global migration and multicultural interactions, this study delves into the linguistic dimensions of cultural identity among Bangladeshi international students in China. The study employs a 20-question survey to examine the role of code-switching, bilingualism, and linguistic choices in identity formation and expression. The dataset includes 65 students from 34 disciplines. One of the major conclusions is that people are ambivalent, particularly about the sense of cultural identity mediated through multilingualism, although there was a strong correlation between cultural expression and use of the mother tongue. The huge proportion of these participants admitted the use of certain linguistic features in different sociolinguistic situations, nevertheless, the importance of English and Mandarin used in the educational contexts emphasized the global and local linguistic dynamics. In order to overcome the drawbacks of this study, future studies must aim to explore the longitudinal impact of settling down in unfamiliar language territories on people’s cultural orientation. Furthermore, this study recommends to take note of the growing need for engaging in acceptable linguistic behavior for the protection and promotion of cultural identity and appreciation among different societies.